2016
DOI: 10.1161/strokeaha.116.013195
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum Phosphate Levels and Stroke Risk in Patients Undergoing Hemodialysis

Abstract: Background and Purpose-The contribution of serum phosphate levels to stroke risk in dialysis patients remains unclear.The present study aimed to elucidate the respective association between serum phosphate levels and the risk of brain hemorrhage or infarction in patients undergoing hemodialysis. Methods-A total of 3437 patients undergoing hemodialysis were followed up for a median of 3.9 years. The primary outcome was the occurrence of brain hemorrhage or infarction. Patients were divided into 4 groups based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 37 publications
4
39
1
1
Order By: Relevance
“…Hypophosphatemia can cause glucose intolerance and tissue insensitivity to insulin [31]. One study revealed that lower serum phosphorus is accompanied by an increased percentage of diabetes mellitus [19]. Our study showed that diabetic patients with stroke had a lower serum level of phosphorus than diabetic patients of the control group.…”
Section: Controlmentioning
confidence: 44%
See 2 more Smart Citations
“…Hypophosphatemia can cause glucose intolerance and tissue insensitivity to insulin [31]. One study revealed that lower serum phosphorus is accompanied by an increased percentage of diabetes mellitus [19]. Our study showed that diabetic patients with stroke had a lower serum level of phosphorus than diabetic patients of the control group.…”
Section: Controlmentioning
confidence: 44%
“…Another study with a 3.9-year follow-up of 3437 patients undergoing hemodialysis reported that a lower serum phosphorus level can cause ischemic stroke and that a higher phosphorus level can cause hemorrhagic stroke. The mechanism is that a higher level of phosphorus triggers inflammatory cytokines and ruptures atherosclerotic lesions, similar to mechanisms that cause coronary artery disease (CAD) [19]. Conditions such as end-stage renal disease put patients in higher serum phosphorus level in the long term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each disease was defined as previously described. [14][15][16] Briefly, stroke was defined as sudden onset of a nonocclusive and focal neurologic deficit persisting for more than 24 hours. Myocardial infarction was defined as a diagnosis based on prolonged severe chest pain, elevated levels of abnormal cardiac biochemical parameters, diagnostic electrocardiographic changes, and morphologic changes (including local asynergy of cardiac wall motion on electrocardiography or a persistent perfusion defect on cardiac scintigraphy).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, people with CKD (particularly black patients) appear to have a greater presence and number of CMB, further increasing their vulnerability 23. Mineral and bone abnormalities may also play a role since higher serum phosphate levels in these patients have been associated with an increased ICH risk, whereas low levels have been associated with an increased risk of cerebral infarction in haemodialysis patients 24…”
Section: Associations Between Ckd and Cerebrovascular Diseasementioning
confidence: 99%